Surgical Application of the Suboccipital Subtonsillar Approach to Reach the Inferior Half of Medulla Oblongata Tumors in Adult Patients - Rabadán, Alejandra T.; Campero, Alvaro; Hernández, Diego (Frontiers in Surgery, 2016)
Abstract Medulla oblongata tumors are uncommon in adults. Controversies about their treatment arise regarding the need for histologic diagnosis in this eloquent area of the brain, weighing benefits of a reliable diagnosis and the potential disadvantages of invasive procedures. As a broader variety of pathological findings could be found in this localization; the accurate histopathological definition could not only allow an adequate therapy, but also can prevent the disastrous consequences of empiric treatments. There are few publications about their surgical management and all belongs to small retrospective cohorts. In this scenario, we are reporting two patients with exophytic or focal lesions in the inferior half of the medulla, who underwent surgery by suboccipital midline subtonsillar approach. This approach was not specifically described to reach medulla oblongata before, and we found that the lesions produced a mild elevation of the tonsils providing a wide surgical view from the medulla to the foramen of Luchska laterally, and up to the middle cerebellar peduncle, offering a wide and safe access.